Acellular porcine placental membranes as a novel biomaterial for tissue repair applications - Almeida, Gustavo Henrique Doná Rodrigues; Lima, Luan Stefani; Gibbin, Mariana Sversut; Lopomo, Beatriz; Bergamo, Rafael Oliveira; da Silva, Raquel Souza; Santos, Giovanna Vitória Consani; Silva, Bruna Gomes; D’Onofrio, Isabela Paulillo; dos Santos, Henrique; Silva, Lediane Pedroso; da Silva, Tais; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
Biological dressings derived from the extracellular matrix (ECM) of human placental tissues have proven effective in treating complex skin wounds and other anatomical sites, offering potential for new therapeutic applications. However, the use of human tissues is limited by ethical and biosafety concerns, restricting large-scale production. To address this, biomaterials from placentas of livestock animals offer a cost-effective, accessible alternative without harming animal welfare. Given pigs’ large-scale production, short gestation periods, and abundant material availability, this study aimed to produce, characterize, and validate acellular biomembranes derived from decellularized porcine allantochorion for tissue repair. Placental fragments from Duroc sows were decellularized using a protocol involving immersion and orbital shaking in 0.1% SDS and 0.5% Triton X-100, followed by low-frequency ultrasonication. Accelularity was confirmed by total genomic DNA quantification and H&E and DAPI staining for nuclear visualization. Membrane structure and composition were analyzed using histological, immunohistochemical methods, and scanning electron microscopy. Spectroscopic analyses detected physicochemical changes in placental ECM, and biomechanical testing assessed membrane strength and stiffness. Biological functionality was validated through in vitro cell viability and adhesion assays with canine endothelial progenitor cells and L929 murine fibroblasts. In vivo biocompatibility was tested by subcutaneously implanting the biomaterial in rats for histopathological evaluation. Results showed efficient decellularization, with preserved ECM structure. The scaffolds were cytocompatible, supporting cell adhesion and high viability. In vivo testing revealed no immune rejection, confirming biocompatibility and biodegradability. In conclusion, acellular porcine placental biomembranes have the necessary characteristics to be explored as scaffolds for tissue engineering and novel repair therapies.